Glycerol monolaurate in the diet of broiler chickens replacing conventional antimicrobials: Impact on health, performance and meat quality - Fortuoso B.F.* (2019)
© 2019 Elsevier LtdGlycerol monolaurate (GML), known as lauric acid, is a chemical compound formed from lauric acid and glycerol that presents strong antimicrobial activity. Therefore, our hypothesis is that MGL can replace conventional antimicrobials, being a new alternative to poultry farming. The aim of this study was to evaluate whether the addition of GML as a replacement for antibiotics could have positive effects on health and performance of broiler chickens. For this, 240, one-day-old, Cobb 500 broiler chicks were weighed and randomly distributed into four groups with four repetitions each (n = 15). The control group, T0, received a basal diet containing antibiotic (60 ppm of bacitracin), while the T100, T200, and T300 groups received a basal diet supplemented with 100, 200, and 300 mg/kg of GML, respectively. The birds were weighed at intervals of seven days, as well as at the end of the experiment (day 42). Blood samples were collected for evaluating animal health, stool for counting bacteria and coccidian, as well as muscle (chest) to measure meat quality, respectively. At the end of the experiment (day 42), body weight, weight gain, and daily weight gain of broiler chickens in the T300 group were higher than the T0 group (P < 0.05). Indeed, feed conversion was lower compared to T0. Animals that received diets containing GML showed lower amounts of Eimeria spp. oocysts on day 42 in comparison to the control group. Low total bacterial counts on day 21 of the experiment were also observed in the treated groups. Conversely, plasma levels of total protein, globulins, uric acid, and glucose were higher in animals that received GML when compared to the control group. It was also observed higher carcass yields in the breast muscle of the T100 group when compared to other groups. Lower water holding capacity was observed in breast meat of animals of the groups T100, T200, and T300 when compared to T0. Histopathological findings were compatible with coccidiosis, and the degree of these lesions did not differ among groups. Based on these results, GML in the diets of broiler chickens, showing potent antimicrobial effect, growth promoter capacity, and lack of toxicity. Therefore, GML is a promising alternative to replace conventional antimicrobials used in the diets of broiler chickens.